Análise estrutural e fadiga em prótese implanto-suportada unitária através do método dos elementos finitos - Hernandez, Bruno Agostinho [UNESP] (2015)
The Biomechanical Engineering consists in the application of engineering concepts in order to developd and to adapt equipments to help in the maintenance and in the support of the life. One of the fields of Biomechanical Engineering is on dental prostheses studies. The dental prostheses are typical biomechanical structures because they restitute the mastification function and they are responsible in replace damaged components. In dental prostheses studies, the experimentation process are, sometimes, hard to preceed due to biological characteristics and, many times, an analytical solution is difficult to achieve. On the other hand, the advances in computer allow the use and implementation of numerical methods, as the Finite Element Method (FEM). By FEM, nonlinear situations can be evaluated, like in dental prostheses cases. Furthermore, the uses of this method allow failure evaluation and its forecast occurrence. The cyclic nature of the loading which the dental prostheses components are exposed means that fatigue failures are the type of failure which needs more attention int these kinds of structures. The aim of this research was to develop a Finite Elment model of single implant-supported prosthesis, by image acquisition and manipulation techniques, to check the model functionality, by experimental and numerical analysis comparison, and then, to do a numerical simulation in order to study the failure in prosthesis' screws. The prosthesis will be compounded by a single implant, an abutment's screw, an abutment, a fixation's screw and a single crown. The results showed that image acquisition, Micro-CT and scanning, are able to construct a complex geometry, like dental prostheses, because the numerical results were checked by experimental procedures. The results from fatigue analysis demonstrated that abutment screw will have finite life in the most of failures criteria analyzed and the fixation screw will be an infinite life in all...